Tinjauan Yuridis Pelindungan Hukum Bagi Pemilik Merek Dikaitkan Dengan Implementasi Asas Contante Justitie Dalam Penyelesaian Perkara Pidana Merek di Indonesia - Elsa Benia; Rika Ratna Permata; Sudaryat (Sanskara Hukum dan HAM, 2023)
The process of resolving brand criminal cases in court still refers to the principles of good justice, including the principle of contante justitie (simple, fast, and low cost). In practice, brand criminal cases were found that did not perfectly implement the principle of contante justitie for example the case of counterfeiting the Cressida and Damor brands which was decided by way of Central Jakarta District Court Decision Number 1778/Pid.B/2011/PN.JKT.Pst. The implementation of the contante justitie principle in the process of resolving trademark criminal cases is not optimal so that legal protection for brand owners who experience violations of trademark rights is difficult to obtain legal certainty. This condition occurs because there are obstacles both in terms of positive law which have not optimally regulated the settlement of criminal cases, especially brands and parties who are less cooperative in carrying out the case settlement process and trial agenda.